PENERAPAN PEMBELAJARAN HIGHER ORDER THINKING SKILLS (HOTS) DI SEKOLAH DASAR - Deri Hendriawan; Usmaedi usmaedi (JURNAL PENDIDIKAN DASAR SETIA BUDHI (JPDS), 2019)
Based on the results obtained from the first cycle to the second cycle, it can be concluded that the use ofimage media can improve the learning outcomes of IPS students in grade III A MIN 4 Serang, the districtof Pamarayan district, attack. Images of media used in this study are images of natural and artificialenvironments. In the learning process the image media is used in the initial activities, core activities andfinal activities in the first cycle, the use of picture media in social studies can improve student learningoutcomes from the class average value of 65.76 to 71.92 and if using the KKM achievement value this hasreached KKM. Then in the second cycle, the average value of students increased again to 76.90. Thisvalue has reached KKM and has reached a target where more than 75% of students get scores of morethan 70.00. Observation results of student tolerance, from cycle I to cycle II improve gravity. This isevidenced by the increased activity of students. From this description, it can be concluded that thelearning outcomes and activeness of class III MIN 4 attacks increased by using media images on socialstudies subjects. With media images students are increasingly eager to learn greetings in class. Keywords: The Use of Media Images, Result Learning Social Science AbstrakBerdasarkan hasil yang diperoleh dari siklus pertama ke siklus kedua, dapat disimpulkan bahwapenggunaan media gambar dapat meningkatkan hasil belajar bagi siswa di kelas III A MIN 4 Serang,kabupaten Pamarayan, serangan. Gambar media adalah gambar lingkungan alami dan buatan. Dalamproses pembelajaran, media gambar dapat digunakan untuk meningkatkan pembelajaran siswa. Hasilbelajar siswa dari nilai rata-rata kelas 65,76 hingga 71,92 dan jika menggunakan nilai prestasi KKM telahmencapai KKM. Kemudian pada siklus kedua, nilai rata-rata siswa meningkat lagi menjadi 76,90. Nilaiini telah mencapai KKM dan telah mencapai target di mana lebih dari 75% siswa mendapat skor lebihdari 70,00. Hasil pengamatan toleransi siswa, dari siklus I ke siklus II meningkatkan gravitasi. Inidibuktikan dengan meningkatnya aktivitas siswa. Dari uraian ini, dapat disimpulkan bahwa hasil dankegiatan pembelajaran telah ditingkatkan oleh gambar media pada mata pelajaran IPS. Dengan gambarmedia, siswa semakin bersemangat untuk belajar salam di kelas. Kata kunci: Penggunaan Media Gambar, Hasil Belajar IPS